Inflation is a social malady - Beigie, Carl E.; British-North American Committee ([London ; Washington, D.C.] : British-North American Committee, 1979)
The book gives a somewhat unsystematic account of the problems of economic policy encountered by OECD countries in the I970s, and advocates as a means of combatting inflation the gradual reduction of monetary growth together with attempts to speed up the rate of productivity growth
Includes bibliographical references.
usc 15/05/18
Loans
Keywords: Inflation (Finance); Economic policy